Swelling pressure of clayey geomaterials: A comprehensive analysis of experimental methods, numerical estimates and molecular dynamics simulations - Mhamdi Alaoui, Hamza; Zhao, Chaofa; Niu, Wenbo; Wu, Daojia; Hicher, Pierre-Yves (Applied clay science, 2025)
Clay minerals are prevalent in clayey soils and rocks, where their swelling behavior upon chemo-thermo-hydro-mechanical forces is critical in geotechnical and geological engineering. Understanding swelling pressure is essential for accurately predicting swelling behavior. Numerous methods have been developed to estimate swelling pressure at different scales, though a comprehensive review comparing these methods is currently lacking. These methods generally fall into three categories: experimental techniques, numerical models, and molecular dynamics simulations. Experimental methods typically involve classical geotechnical tests, such as oedometer tests, conducted under varying loading conditions. Numerical models aim to simulate chemo-hydro-mechanical interactions, with particular emphasis on double-layer swelling. Recently, data-driven models have demonstrated high accuracy and good alignment with experimental findings. Molecular dynamics simulations provide insights into swelling behavior at the molecular scale, often correlating well with macroscale experimental results. This review summarizes these methods by detailing their key principles, recent advancements, challenges, and differences. It concludes with guidance on selecting the most suitable methodology for characterizing swelling pressure, tailored to the specific focus and requirements of each study. •Microstructural insights into swelling pressure of clayey geomaterials are provided.•Swelling pressure of clayey geomaterials is quantified across different scales.•Physics- and data-based estimates are validated by experimental results.•Swelling pressure of clays has been estimated by molecular dynamics simulations.